PENGARUH KEGIATAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA TERHADAP SIKAP MANDIRI SISWA DI SMA DIPONEGORO 2 - Risma, Risma; Sutiono, Sutiono; Shofiyat, Ali Ilham (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
The Project Activity for Strengthening the Pancasila Student Profile is expected to form the personality of Indonesian students based on the values of Pancasila, one of the values contained in the Pancasila Student Profile is an independent attitude. Therefore, students are expected to take part in project activities to strengthen the Pancasila Student Profile. This research aims to determine the influence of the Pancasila Student Profile Strengthening Project Activities on Students' Independent Attitudes at SMA DIPONEGORO 2. The aim of the research is to find out and understand the influence of the Implementation of the Pancasila Student Profile Strengthening Project on Students' Independent Attitudes.The method used in this research is quantitative correlational with a sample of 64 students using a simple random sampling technique. The analysis technique uses simple linear regression and correlational tests. Based on the research results, it can be concluded that project activities to strengthen the Pancasila Student Profile have an influence on students' independent attitudes. This is shown by the results of the hypothesis test using the Pearson Product Moment correlation, with a significance value of 0.000 (0.000 < 0.05) and a Pearson correlation value of 0.557 (0.40-0.599), which shows that there is a very strong correlation. Thus, it can be concluded that the higher the level of activities of the Pancasila Student Profile Strengthening Project, the better the level of independent attitude of the students. On the other hand, the low level of Pancasila Student Profile Strengthening Project activities among students will have a negative impact on students' independent attitudes.